Anti-hypertensive therapy as a basis for neuroprotection in modern clinical practice - V. N. Shishkova (Лечащий Врач, 2021)
Contemporary guidelines on treatment of arterial hypertension and the data on clinical efficiency of use of four-component neuroprotective preparation were studied. The combination of its components — enalapril, indapamide, and Metoprolol Tartrate ensures versatile organ-protective support and enhances the forecast, and nootrope vinpocetine potentiates anti-hypertensive effect and improves condition of cerebral circulation.